Age and growth of Jack mackerel Trachurus murphyi in Peru - Dioses, Teobaldo (2013)
The age and growth of Jack mackerel Trachurus murphyiNichols 1920 was determined by the reading and measuring annual growth rings from 977 pairs of otoliths from specimens between 3 and 71 cm total length collected within the Peruvian maritime domain during 1978 and part of 1977 and 1979. The validity of the annual marks was confirmed with 50 otolith with 5 marks or annual zones, and also with the analysis of the monthly marginal increment in 240 otoliths of specimens between 35 and 39 cm obtained from July 1977 to June 1979. From the annual rings measurements and their respective retroestimated sizes, the following parameters of the von Bertalanfy ecuation for growth in length and weight were estimated: infinite length (L ∞ ) = 80.77 cm, infinite weight (W∞ ) = 3744.10 g, growth coefficient (k) = 0.155, and theoretical age at length 0 (t 0 ) = –0.356. The estimated parameters suggest that the Peruvian T. murphyi has a faster growth rate than the more southern T. murphyi.